The Effect of Inflation and Efficiency on Performance Indonesian Sharia Commercial Bank - Ani Setyawati; Haqiqi Rafsanjani; Luluk Latifah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to analyze the influence of inflation and efficiency on the performance of sharia banking in Indonesia, as measured by Return on Assets (ROA). The data used is monthly time series data from 2014 to 2023 obtained from the Financial Services Authority (OJK) and Bank Indonesia (BI). The analysis method used is the Vector Error Correction Model (VECM) to identify short-term and long-term relationships between variables. The research results show that inflation has a significant influence on sharia banking profitability in the short term, but does not have a significant impact in the long term. In contrast, operational efficiency, as measured by the ratio of Operating Costs to Operating Income (BOPO), has a greater impact on Islamic banking profitability than inflation. These findings confirm that increasing operational efficiency is the main factor in maintaining the positive performance of Islamic banking amidst economic fluctuations.